The Effects of Principals’ Leadership, School Culture, and Work Motivation on the Professionalism of Elementary School Teachers - Debariyani, Ninik; Nurkolis, Nurkolis; Rasiman, Rasiman (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze the influence of school principal leadership, school culture, and work motivation on teacher professionalism in public elementary schools. The population of this study comprised all public elementary school teachers in the Gunung Wungkal District, totaling 155 teachers, from which a sample of 112 respondents was selected used Slovin formula. Data were collected through questionnaires and documentation. The data analysis techniques employed included descriptive data analysis and hypothesis testing, which encompassed simple and multiple linear regression analyses. Data analysis was conducted using SPSS. The results: (1) principals’ leadership has a significant partial effect on teacher professionalism, with a correlation coefficient of 0.676  and a contribution of 45.7%; (2) school culture has a significant effect on teacher professionalism, with a correlation coefficient of 0.621  and a contribution of 38.6%; (3) work motivation has a significant effect on teacher professionalism, with a correlation coefficient of 0.615  and a contribution of 37.8%; and (4) principals’ leadership, school culture, and work motivation simultaneously have a significant effect on teacher professionalism, with a correlation coefficient of 0.763 (strong category) and a contribution of 58.2%.